Optimalisasi Rencana Perguruan Tinggi Melalui Perencanaan Strategis Sistem Informasi (IS) - Addin Gama Bertaqwa; Sunardi; Uswatun Hasanah (Journal of Computer Science and Informatics Engineering (J-Cosine), 2023)
This study is motivated by the policy of a university related to Information System (IS) or Information Technology (IT) which was prepared without careful planning so that the information system that had been built did not fully support the university’s plan according to the university strategic plan. Therefore, the purpose of this research is to be able to implement an information system that is optimal and in line with the university strategic policies, so strategic planning of IS is needed. This is done so that the investment spent on IS development is accordance with the needs and can provide measurable benefits in accordance with the goals and objectives of the university. This study uses PEST, SWOT, Value Chain, and Critical Success Factor analysis. Then determine the IS/IT strategic plan and it is expected to produce outputs in the form of IS/IT strategic planning proposals at Campus X. Therefore, based on the results of the McFarlan Strategic Grid mapping which states that of the 6 existing IS applications, none of the applications are in the Strategic quadrant and the High Potential quadrant. The result of the IS/IT strategic planning shows that there are 12 new IS applications, the development of new network infrastructure as well as the addition of new human resources.